The Expected vs Actual perception of students entering clinical environment: A pilot study - Daniel Ardian Soeselo; Sandy Theresia; Ryan Austin (Tarumanagara Medical Journal, 2021)
Students’ perceptions regarding the learning environment can be used in improving the quality of the learning environment. This study aims to evaluate the differences between expected and actual learning environment perceptions of students after going through a clinical rotation. This pilot study is an observational descriptive study that was conducted in the Medical Faculty of Atma Jaya Catholic University of Indonesia on students that have completed pre-clinical education and have entered clinical rotation in January – March 2020. This study used the Dundee Ready Education Environment Measure (DREEM) questionnaire. The data was collected from 59 students and was analyzed using SPSS 23.0. The total actual DREEM score was better than the total expected DREEM score. In the Students’ Academic Self-Perceptions (SASP) domain, there was a decrease in the actual DREEM score. Meanwhile, there was an increase in the Students’ Percepstions of Teachers (SPT) domain which was statistically significant. The actual DREEM score in the Students’ Perceptions of Learning (SPL) domain also showed better results in males than females (P < 0.05). Quality improvement and continuous innovation are very important in medical education.